Institutionalist versus distortionist views of labor market reforms: An investigation into the post-liberalized manufacturing sector in India - Kumar Bhandari, Anup (2016)
Labor regulation and employment relation has been investigated in India in light of the seminal work ofBesley and Burgess (2004), considering formal sector manufacturing employment as the explained vari-able. Empirical findings support, although not very strongly, the institutionalist view, i.e., pro-workeramendment in labour laws induces employment. Among the other factors, real wage rate has significantnegative effect on employment, whereas that for real per capita developmental capital expenditure, percapita electricity generation capacity and real per capita net state domestic product is significant positive.However, effect of per capita real developmental revenue expenditure is inconclusive. In other words,although it improves employability of workers through their human capital improvement, which is prob-ably met up at the cost of worsening overall infrastructural development, through reducing correspondingcapital expenditure! Supporting evidence has also been provided favoring this conjecture.